Participación e inclusión social de grupos de atención prioritaria en la comuna San José del cantón Santa Rosa. año 2020 - Aguilar Castro, María Andrea; Delgado Vélez, Josselyne Lilibeth (Machala: Universidad Técnica de Machala, 2021)
The present investigative work called Participation and Social Inclusion of Priority Attention Groups in the San José of the Canton Santa Rosa commune, Year 2020, a problem that has been occurring at the local, national and global level, where these groups that according to their Special needs are considered vulnerable and where the state that represents them is in charge of designing public policies that ensure that their rights are respected and in addition to providing them with an optimal quality of life. The main objective of this research is to identify the participation and social inclusion of priority attention groups in the San José commune of the Santa Rosa canton, through the characterization of this population, to propose relevant alternatives with the improvement of their socioeconomic conditions. The methodology of this research is of a mixed nature, a combination of quantitative and qualitative, subject to the inductive-deductive method, using the survey technique which was applied to the 122 heads of household in the San José commune, from In the same way, an interview was carried out with the main directors of the Pro-improvement committee, as well as a direct observation guide that made it possible to verify the problems that said community has and bibliographically complemented the information collected. The results obtained in this research determine that priority attention groups are not taken into account in the decision-making and activities carried out by the directors of the Pro-Improvement Committee, that is, they have a low level of social participation within their community, a situation that affects their personal and community development. In addition to the fact that the inhabitants of the San José commune do not have knowledge about the public policies that they possess and protect this group of people in vulnerable situations. Another result is the lack of knowledge that the directors of the San José commune have on community management issues, which is why in recent years there have not been implemented projects or programs of great relevance that benefit all the inhabitants of the site and with greater emphasis on providing solutions to the problems faced by priority attention groups. In the same way, most of these people who are in some situation of vulnerability do not have the socioeconomic support from government entities, evidencing the abandonment and unconcern towards this community. Due to the need that this community is going through, the present Educational Proposal in socio-legal rights for the inclusion and participation of priority attention groups of the San José commune has been designed, which aims to increase the level of intervention of these people in the social, cultural, economic and political environment of the site. The implementation of this proposal will directly benefit the priority care groups and indirectly all the inhabitants of the San José commune, which will contribute to the awareness of the community about the care and protection that these people need, according to the established planning. Training and workshops will be developed which will be given by professionals on the subject, in this way the pertinent knowledge about vulnerable groups will be provided in a responsible manner.
El presente trabajo investigativo denominado Participación e Inclusión Social de Grupos de Atención Prioritaria en la comuna San José del Cantón Santa Rosa, Año 2020, problemática que se viene dando a nivel local, nacional y mundial, donde estos grupos que de acorde a sus necesidades especiales son considerados vulnerables y el estado que los representa son los encargados de diseñar políticas públicas que aseguren que sus derechos sean respetados y además brindarles una óptima calidad de vida. El objetivo principal de esta investigación es Identificar la participación e inclusión social de los grupos de atención prioritaria en la comuna San José del cantón Santa Rosa, a través de la caracterización de esta población, para proponer alternativas pertinentes con el mejoramiento de sus condiciones socioeconómicas. La metodología de la presente investigación es de carácter mixto, combinación entre lo cuantitativo y cualitativo, con sujeción al método inductivo – deductivo, utilizando la técnica de la encuesta la cual se la aplico a los 122 jefes de hogar de la comuna San José, de la misma manera se realizó una entrevista a los principales directivos del comité Pro-mejores, además de una guía de observación directa que permitió constatar los problemas que tiene dicha comunidad y complementado bibliográficamente la información recolectada. Los resultados obtenidos en la presente investigación, determinan que los grupos de atención prioritaria no son incluidos en la toma de decisiones y actividades que realizan los directivos del Comité Pro-mejoras, es decir poseen un bajo nivel de participación social en su comunidad, situación que afecta su desarrollo personal y comunitario. Además de que los habitantes de la comuna San José no tienen conocimiento acerca de las políticas públicas que poseen y amparan a este grupo de personas en situación de vulnerabilidad. Otro de los resultados, es el desconocimiento que los directivos de la comuna San José poseen en temas de gestión comunitaria, razón por la cual en los últimos años no se ha implementado proyectos o programas de gran relevancia que beneficien a todos los habitantes del sitio y con mayor énfasis en dar soluciones a los problemas que atraviesan los grupos de atención prioritaria. De igual manera la mayoría de estas personas que se encuentran en alguna situación de vulnerabilidad no cuentan con el apoyo socioeconómico por parte de entidades gubernamentales evidenciando el abandono y despreocupación hacia esta comunidad. Debido a la necesidad que atraviesa esta comunidad se ha diseñado la presente Propuesta educativa en derechos socio-jurídicos para la inclusión y participación de los grupos de atención prioritaria de la comuna San José que pretende incrementar el nivel de intervención de estas personas en el entorno social, cultural, económico y político del sitio. La implementación de esta propuesta beneficiará directamente a los grupos de atención prioritaria e indirectamente a todos los habitantes de la comuna San José, la cual aportará a la sensibilización de la comunidad sobre el cuidado y protección que necesitan estas personas, de acorde a la planificación establecida se desarrollaran procesos de capacitación los cuales serán impartidos por profesionales del tema, brindando de manera responsable los conocimientos pertinentes acerca de los grupos vulnerables.
Keywords: COMUNIDAD; VULNERABILIDAD; GESTION; IGUALDAD